A Novel Design of Microstrip Antenna for Microwave Imaging Application. Issue 8 (28th May 2013) - Ojaroudi, Nasser; Ojaroudi, Mohammad
ABSTRACT In this article, a novel ultrawideband printed monopole antenna for microwave imaging systems is presented. The proposed antenna provides a wide usable fractional bandwidth of more than 160% (2.12–17.87 GHz). The antenna has an ordinary square radiating patch, therefore displays a good omnidirectional radiation pattern even at higher frequencies and also its radiation efficiency is greater than 82% across the entire radiating band. The designed antenna has a small size of 12 × 18 mm2. © 2013 Wiley Periodicals, Inc. Microwave Opt Technol Lett 55:1755–1758, 2013